Integrating Al-‘Urf into Smart Contracts: Addressing Regulatory Challenges in Blockchain-Based Waqf Governance (Jurnal Hukum Islam, 2026)
The integration of blockchain technology into waqf system opens opportunities for transforming digital waqf governance by increasing transparency, efficiency, and accountability. Despite the potential, its implementation still faces Sharia compliance issues and regulatory challenges. Therefore, this study aims to examine the feasibility of implementing smart contracts, identify the regulatory challenges of smart contracts in blockchain-based waqf governance, and propose integrating Al-‘Urf as a model to support adaptive and sustainable governance. The study procedures were carried out using a normative juridical method with a statutory and conceptual approach. Legal materials, such as regulations, fiqh documents, fatwas, literature, and whitepapers on blockchain-based waqf, were then analyzed. The results showed that smart contracts had the technical potential to strengthen the transparency and efficiency of waqf management. However, its effectiveness depended on protocol security, code quality, and verification mechanisms to ensure compliance with the principles of justice ('adl), the prohibition of gharar, and usury. Regulatory challenges were primarily from the lack of regulations on the status of digital assets, the validity of blockchain-based contracts, and the dispute-resolution mechanism for digital waqf, creating legal uncertainty. Al-‘Urf integration through taqnin and siyasah syar‘iyyah could form the basis for developing more adaptive and sustainable digital waqf regulations. These results are expected to contribute to the development of a digital waqf governance model based on 4 components, including normative foundation, governance architecture, sustainable investment, and policy coherence. The model integrates Sharia principles, blockchain governance, and adaptive regulation as a new paradigm in the digital economy era.
Keywords: Al-‘Urf; Blockchain; Digital Waqf; Sharia Compliance; Smart Contract